Comparison of weekly and daily online adaptation for head and neck intensity-modulated proton therapy. (25th February 2021) - Bobić, Mislav; Lalonde, Arthur; Sharp, Gregory C; Grassberger, Clemens; Verburg, Joost M; Winey, Brian A; Lomax, Antony J; Paganetti, Harald
Abstract: The high conformality of intensity-modulated proton therapy (IMPT) dose distributions causes treatment plans to be sensitive to geometrical changes during the course of a fractionated treatment. This can be addressed using adaptive proton therapy (APT). One important question in APT is the frequency of adaptations performed during a fractionated treatment, which is related to the question whether plan adaptation has to be done online or offline. The purpose of this work is to investigate the impact of weekly and daily online IMPT plan adaptation on the treatment quality for head and neck patients. A cohort of ten head and neck patients with daily acquired cone-beam CT (CBCT) images was evaluated retrospectively. Dose tracking of the IMPT treatment was performed for three scenarios: base plan with no adaptation (BP), weekly online adaptation (OAW ), and daily online adaptation (OAD ). Both adaptation schemes used an in-house developed online APT workflow, performing Monte Carlo dose calculations on scatter-corrected CBCTs. IMPT plan adaptation was achieved by only tuning the weights of a subset of beamlets, based on deformable image registration from the planning CT to each CBCT. Although OAD mitigated random delivery errors more effectively than OAW on a fraction per fraction basis, both OAW and OAD achieved the clinical goals for all ten patients, while BP failed for six cases. In the high-risk CTV, accumulated values of D 98% ranged between 97.15% and 99.73% of the prescription dose for OAD, with a median of 98.07%. For OAW, values between 95.02% and 99.26% were obtained, with a median of 97.61% of the prescription dose. Otherwise, the dose to most organs at risk was similar for all three scenarios. Globally, our results suggest that OAW could be used as an alternative approach to OAD for most patients in order to reduce the clinical workload.